An evaluation of the suitability of different electrode arrays for geohydrological studies in Karoo rocks using electrical resistivity tomography - Tamssar, Arnaud Hamidou (University of the Free State, 2013)
The suitability of different electrodes arrays used during electrical resistivity tomography surveys for geohydrological studies in the Karoo rocks is evaluated through theoretical considerations, numerical modelling and field surveys. The theoretical considerations predict that the Wenner array is sensitive to vertical changes in resistivity in the subsurface, while the Dipole-Dipole array is sensitive to horizontal changes in resistivity and the Schlumberger array is sensitive to both vertical and horizontal changes in resistivity. The theoretical considerations also show that the arrays with the strongest signal strength, the greatest depth of investigation and the broadest horizontal data coverage are the Wenner, the Dipole-Dipole and the Pole-Pole arrays, respectively. Twenty synthetic geological models, simulating dolerite dyke and sill intrusions, weathered zones, faults zones or bedding plane fractures and different types of geological boundaries, are used to evaluate the sensitivity, depth of investigation, signal strength, as well as horizontal data coverage of the Wenner, Schlumberger, Dipole-Dipole and Pole-Pole arrays. Responses of these numerical models to the L1-norm, L2-norm and to random noise are also investigated. Numerical modelling results indicate that the Wenner array is sensitive to vertical changes in the Earth’s subsurface resistivity, has the strongest signal strength, yet the shallowest depth of investigation and the narrowest horizontal data coverage. The Schlumberger array, sensitive to both vertical and horizontal resistivity changes in the subsurface, has high signal-to-noise ratio and better depth coverage compared to the Wenner array. The Dipole-Dipole array is seen to be sensitive to horizontal resistivity changes in the subsurface, has great depth penetration, but a low signal-to-noise ratio. Although the Pole-Pole array has the broadest horizontal data coverage and the greatest depth of investigation this array is the most vulnerable to noise contamination. The robust constraint inversion (L1-norm) should be selected for inverse modelling if the goal of the surveys concerns groundwater exploration since this algorithm produces models with sharp boundaries between different geological bodies. Conversely, the smoothness-constrained least-squares inversion (L2-norm) is appropriate when studying groundwater migration and contaminant transport because the diffusion boundary of a contaminant plume in the subsurface geology is likely to be associated with a smoother variation in the resistivities. The L2-norm inversion method gives optimal results under such conditions where gradual changes in the subsurface resistivities are expected. Two-dimensional electrical resistivity tomography surveys were carried out at three different sites near the city of Bloemfontein where dolerite dyke and sill intrusions occur. Results showed that the Wenner array is the most suitable electrode array to use for field surveys conducted across sill intrusions, while the Schlumberger array is the most appropriate for field surveys over dyke intrusions or sills intruded by dykes. The Dipole-Dipole array presented significant limitations for the field investigations due to its low signal-to-noise ratio. Results from the field studies conducted around Bloemfontein are in agreement with theoretical considerations as well as numerical modelling except the minor limitation of the Dipole-Dipole array (array recommended in theory by some authors). Results demonstrate that the two-dimensional electrical resistivity tomography surveys employing either the Wenner or Schlumberger arrays, in conjunction with the appropriate inversion technique, would be of great benefit to geohydrological studies in Karoo rocks, particularly for boreholes siting and during contaminant transport studies.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2013
Keywords: Groundwater -- South Africa -- Karoo; Hydrogeology; Tomography; Dykes; Sills; Geohydrological studies; Karoo rocks; Electrical resistivity tomography; Electrode arrays; Suitability